2023
DOI: 10.1021/acsaem.2c04168
|View full text |Cite
|
Sign up to set email alerts
|

Large-Area WO3/BiVO4-CoPi Photoanode for Efficient Photoelectrochemical Water Splitting: Role of Patterned Metal Microgrid and Electrolyte Flow

Abstract: The WO3/BiVO4 heterojunction-based photoanodes have demonstrated great potential in the field of photoelectrochemical (PEC) water splitting. The advancement in large-area photoanodes is impeded due to the resistive loss of transparent conducting oxide (TCO) substrate, nonhomogeneity in the photoactive films, nonuniform deposition of co-catalyst, and pH gradient across the electrode. Herein, the patterned metal microgrid is sputtered under the WO3/BiVO4 heterojunction to reduce resistive losses and improve the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…Despite the progress made in developing BiVO 4 -based photoelectrodes, their stability remains a critical issue that needs to be addressed. Some studies have suggested that incorporating electrocatalysts, such as CoPi 48,49 and FeNiO x , 50,51 on the surface of BiVO 4 can enhance both the kinetics of oxygen evolution from water and Fig. 7 The identity of the BiVO 4 compound with its main physico-chemical characteristics and properties, crystal structures, and band gap diagram is from Park et al 15 the stability of the electrode by reducing corrosion.…”
Section: Langmuir-blodgett Approach To Scale Up Photoelectrode: Case ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the progress made in developing BiVO 4 -based photoelectrodes, their stability remains a critical issue that needs to be addressed. Some studies have suggested that incorporating electrocatalysts, such as CoPi 48,49 and FeNiO x , 50,51 on the surface of BiVO 4 can enhance both the kinetics of oxygen evolution from water and Fig. 7 The identity of the BiVO 4 compound with its main physico-chemical characteristics and properties, crystal structures, and band gap diagram is from Park et al 15 the stability of the electrode by reducing corrosion.…”
Section: Langmuir-blodgett Approach To Scale Up Photoelectrode: Case ...mentioning
confidence: 99%
“…Despite the progress made in developing BiVO 4 -based photoelectrodes, their stability remains a critical issue that needs to be addressed. Some studies have suggested that incorporating electrocatalysts, such as CoPi 48,49 and FeNiO x , 50,51 on the surface of BiVO 4 can enhance both the kinetics of oxygen evolution from water and the stability of the electrode by reducing corrosion. However, fabricating stable BiVO 4 photoelectrodes in aqueous environments remains an open question.…”
Section: Langmuir–blodgett Approach To Scale Up Photoelectrode: Case ...mentioning
confidence: 99%
“…At present, a variety of processes have been developed through photocatalysis (PC), 24–28 electrocatalysis (EC), 29–33 and photoelectrocatalysis (PEC), 34–39 which use water as a source for hydrogen production and advanced materials as electrodes or catalysts. Electrocatalysis has been widely used in hydrogen production because of its high efficiency, strong adaptability, and easy automatic control.…”
Section: Introductionmentioning
confidence: 99%